The critical roles of α-amylase and amyloglucosidase in improving the quality of black waxy corn beverages: Special attentions to the color and flavor. (March 2023) - Xiang, Yake; Chen, Xiao; Sun, Hailan; Zhan, Qiping; Zhong, Lei; Hu, Qiuhui; Zhao, Liyan
Abstract: To preserve the nutrients while maximizing the value of black waxy corn, beverage is the most promising manufacturing product. However, the poor stability and bland flavor profile are significant issues limiting its popularization. This study, firstly profiled the anthocyanidins of black waxy corn and the effects of α-amylase and amyloglucosidase treatments on the anthocyanidin levels, color properties, and flavor qualities were systematically studied. A total of 5 anthocyanidins and 11 anthocyanins were identified. The concentration of cyanidin, petunidin, peonidin, pelargonidin, and malvidin in liquefied liquids (YHY) and saccharified liquids (THY) were significantly increased by 55.46% and 56.62% after α-amylase and amyloglucosidase treatments. The enzymatic hydrolysis was found to enrich the volatile profile. The relative odor activity value and multivariate statistical analyses further suggested isoamyl acetate, benzaldehyde, 2-nonenal, 2, 4-decadienal, dodecanal, 2-buten-1-one, 3-buten-2-one, and dimethyl trisulfide as key odorants to discriminate black waxy corn beverages produced by α-amylase or amyloglucosidase. Graphical abstract: Image 1 Highlights: Amyloglucosidase significantly altered the color quality of black waxy corn beverage. Both α -Amylase and amyloglucosidase treatments increased the anthocyanidins contents. The flavor properties were significantly enhanced after enzymatic hydrolysis. Fifteen volatiles were selected as markers to discriminate different beverage samples.